Phototoxicity of essential oils intended for cosmetic use - Kejlová, Kristina; Jírová, Dagmar; Bendová, Hana; Gajdoš, Petr; Kolářová, Hana (Toxicology in vitro, 2010)
The aim of this study, linked-up with a previous study on bergamot oils, was the evaluation of phototoxic potential of essential oils (orange, lemon and Litsea cubeba), used as cosmetic ingredients. The applied tiered testing strategy included chemical analysis of the substances (by means of capillary gas chromatography/mass spectrometry), in vitro 3T3 NRU phototoxicity test and EpiDerm™ skin phototoxicity test. In order to clarify the situation in man, the highest non-phototoxic/non-cytotoxic concentrations and concentrations 10 x lower (safety factor 10) were tested xin vivo by means of human skin photopatch test in a limited group of human volunteers. The study revealed, that phototoxicity of the essential oils was dependent on the content of photoactive components and the solvent used. The highest non-phototoxic concentrations obtained by the skin model assay proved to be a useful starting point for subsequent confirmatory human photopatch test aimed to identify safe concentration for human use. However, the highest non-phototoxic concentration obtained in the skin model assay cannot be applied directly for human practice (3 of 8 tested oils evoked a phototoxic reaction). A safety factor of 10 should be applied for extrapolation of experimental data from the skin model assay to man.
Keywords: Oils, Volatile; Skin Tests; fototoxická dermatitida; oleje rostlin; lidé středního věku; Litsea; lidé; Adult; oleje prchavé; Middle Aged; dospělí; Female; Dermatitis, Phototoxic; kožní testy; ženské pohlaví; Plant Oils; Humans; kosmetické přípravky; Cosmetics